The kinematic factors associated with elite level pistol shooting performance - Dadswell, C. E. (Manchester Metropolitan University, 2016)
This thesis considered the kinematic factors associated with elite pistol shooting performance. The first three studies examined performance in the newly introduced modern pentathlon combined event. Study 1 demonstrated that shooting performances differed significantly between the combined event and the original precision shooting format. Pistol shooters achieved significantly higher scores, and significantly smaller pistol and centre of pressure movements, than modern pentathletes in the precision event (p<.05). No significant differences were evident between the groups for combined event shooting (p>.05), highlighting that the most successful precision shooters were not guaranteed success in the combined event. Studies 2 and 3 examined how shooting performance changed within and between each shooting series. Aiming time did not change significantly within any series (p>.05), and so participants experienced a similar degree of pistol and centre of pressure movement for each shot, and achieved similar scores. No significant differences were evident in shooting performances between each shooting series (p>.05), despite the additional 1 km run phases. Thus, each running phase appeared to have little impact on shooting performance. Individual analysis used in each study highlighted the extent of individual variation in shooting performances, and demonstrated that group analysis is not sufficient to reflect the performances of individual participants. The final two studies examined elite precision shooting performances. Study 4 provided a descriptive analysis of torso, shoulder, wrist and pistol movement during the final second before the shot. Participants produced variable movement patterns for the upper limb, reflecting the principle of abundancy, in order to control the motion of the pistol. The exact patterns varied between participants, further supporting the importance of using individual analysis to examine pistol shooting performance. Study 5 examined the effects of stance position on shooting performance. Changing stance position produced significant differences in the scores achieved by each participant (p<.05). The most effective mediolateral and anterior-posterior stance widths, and the mechanisms behind the changes in performance, varied between participants. Thus, it was recommended that pistol shooters should examine stance position in greater detail when attempting to enhance performance.